Peran Agama dan Komunikasi dalam Perkawinan - Hidayani Syam; Ira Revia Restu; Liyoni Janika; Monica Ayudia (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Marriage is a sacred bond recognized by religion and the state. In the context of religion, marriage has a very important role in the life of a Muslim, including the Spiritual Foundation and Worship, Maintaining Pious and Pious Offspring. Marriage in Islam also aims to produce pious and pious offspring. Religion provides guidance on how to educate children with good religious and moral values. In the context of positive law, the state gives authority to the validity or invalidity of a marriage to each religion.Communication in the family is the process of exchanging information, feelings. Communication in the family is the process of exchanging information, feelings, and ideas between family members to create harmonious relationships, mutual understanding, and support each other. The Importance of Communication in the Family is very useful for avoiding conflict in the household. The importance of communication in the family is as follows: Building Harmonious Relationships Good communication strengthens the bonds between family members, creating an atmosphere full of love and mutual understanding.